Heparan sulfate proteoglycans in Drosophila neuromuscular development. - Kamimura, K.; Maeda, N. (Biochimica et Biophysica Acta, 2017)
Heparan sulfate proteoglycans (HSPGs) are glycoconjugates bearing heparan sulfate (HS) chains covalently attached to core proteins, which are ubiquitously distributed on the cell surface and in the extracellular matrix. HSPGs interact with a number of molecules mainly through HS chains, which play critical roles in diverse physiological and disease processes. Among these, recent vertebrate studies showed that HSPGs are closely involved in synapse development and function. However, the detailed molecular mechanisms remain elusive. Genetic studies from fruit flies, Drosophila melanogaster, have begun to reveal the molecular mechanisms by which HSPGs regulate synapse formation at neuromuscular junctions (NMJs). In this review, we introduce Drosophila studies showing how HSPGs regulate various signaling pathways in developing NMJs. This article is part of a Special Issue entitled Neuro-glycoscience, edited by Kenji Kadomatsu and Hiroshi Kitagawa.